UV photodissociation dynamics of iodobenzene: effects of fluorination. - Murdock, D; Crow, M; Ritchie, G; Ashfold, M (2012)
The UV photochemistry of various fluorinated iodobenzenes (4-fluoro-, 2,4-difluoro-, 3,5-difluoro-, and perfluoro-iodobenzene) has been investigated at many wavelengths by velocity map imaging, time-resolved near infrared absorption spectroscopy and (spin-orbit resolved) ab initio calculations of the ground and excited state potentials along the C-I stretch coordinate, R(C-I). The textbook description of the near UV photochemistry of CH(3)I, i.e., σ∗←n excitation to the (3)Q(0+) state, followed by direct dissociation (to yield spin-orbit excited iodine atom (I∗) products) or by non-adiabatic coupling via a conical intersection (CI) with the (1)Q(1) potential (to yield ground state iodine (I) atoms) is shown to provide a good zero-order model for aryl iodide photochemistry also. However, the aryl halides also possess occupied π and low-lying π∗ orbitals, and have lower (C(2v) or C(s)) symmetry than CH(3)I. Both of these factors introduce additional subtleties. For example, excitations to and predissociation of ππ∗ excited states provide additional routes to I products, most obviously at long UV wavelengths. nσ∗∕πσ∗ configuration mixing stabilizes the (analogue of the) (3)Q(0+) potential energy surface (PES), to an extent that scales with the degree of fluorination; the corresponding 4A(1) PES in C(6)F(5)I is actually predicted to exhibit a minimum at extended R(C-I). This has the effect of extending the long wavelength threshold for forming I∗ products. The lowered symmetry enables an additional (sloped) CI with the 5A(2) (9A(") in 2,4-difluorobenzene) PES, which provides an extra non-adiabatic route to (fast) ground state I atoms when populating the 4A(1) PES at shorter UV excitation wavelengths.